Avoidance in intercultural work contexts : the role of language self-efficacy, cultural intelligence, and interpersonal negative affect - Peyrols Wu, Catherine Céline Marie-Françoise (2017)
Avoidance of interactions with people from different cultures is a common occurrence that can have detrimental effects on work collaborations. Yet, we know very little about what can be done to reduce avoidance behaviors in contexts where people from different cultures work together. To address this gap, I developed and tested a model to predict and explain avoidance in intercultural work contexts. Drawing on Social Identity Theory and Affective Events Theory, I propose a model where language self-efficacy and cultural intelligence (CQ) have negative main effects on avoidance behaviors. Further, I hypothesize a joint effect such that avoidance should be the lowest when people are both efficacious to communicate in the language of interaction and culturally intelligent. Next, I hypothesize that interpersonal negative affect should mediate the joint effect of language self-efficacy and CQ on avoidance. I tested my model using two time-lagged field studies. In Study 1, I tested the hypothesized main and joint effects with 108 household service workers using OLS regressions. The findings did not support the main effects of language self-efficacy and CQ but supported the joint effect on avoidance. In Study 2, I tested the main effects, joint effect and mediation in 391 intercultural dyads from a sample of 82 senior business students working in multicultural teams using a round-robin multisource design and social relations modeling analyses. The main effect of language self- efficacy was not supported but the main effect of CQ was significant and negative. The joint effect found in Study 1 was replicated. Further, the joint effect was fully mediated by interpersonal negative affect. I discuss the implications of these findings for theory and practice.